Organizational Justice and Work Motivation: The Perspective of Civil Servant Groups in Banten and Central Java Provinces - Minrohayati, Minrohayati; Tantri, Sakina Nusarifa; Damayanti, Prisila; Siolemba Patiro, Shine Pintor (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The purpose of this study was to uncover the effect of organizational justice (procedural justice, distributive justice, and interactional justice) on the work motivation of BAPENDA employees in Banten and Central Java Provinces. The data were collected using a survey with a purposive sampling technique. The sample size of the study was 587 persons, which involved 200 civil servants at Central Java Province BAPENDA and 387 civil servants at Banten Province BAPENDA. The data were analyzed using multigroup Structural Equation Modeling (SEM). The results of the study showed that organizational justice (distributive, procedural, and interactional justices) can explain and predict the work motivation in the cultural group background of Banten and Central Java. The involvement of the two different cultural groups in this study indicated that the analysis supports the high model fit. In other words, the psychometric properties of the model measurements was not disturbed by the group presence, aka disturbed by the deceptive response.